Pengaruh Strategi Pembelajaran Cooperative Learning Tipe Rotating Trio Exchange Terhadap Prestasi Belajar Matematika Siswa MTS - Muhammad Alwan (Jurnal Al-Muta`aliyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
The purpose of this study was to determine the effect of cooperative learning strategies of rotating trio exchange type learning on mathematics learning achievement of MTs students. This type of research is quasi-experimental, the sampling technique used was purposive sampling consisting of class VIIIb 27 students as the experimental class and class VIIIc 27 students as the control class. While the data collection method used in this study is to use the test method. The analysis used was the t test. The results of data analysis obtained a value = 5.069 at a significant level of 5% obtained with degrees of freedom (dk) 27-2 = 25 is 2.052, because the value> (5.069> 2.052) then the null hypothesis is rejected and the alternative hypothesis is accepted, so it can be concluded there is a strategy effect Rotating trio exchange cooperative learning learning on MTs students' mathematics learning achievement. And the regression equation is Ŷ = 8.621 + 0.744x and the model can be explained by 50.7%.